PHASE TRANSITION AND COMPRESSION BEHAVIOR OF GIBBSITE UNDER HIGH-PRESSURE - Liu H.; Hu J.; Xu J.; Liu Z.; Shu J.; Mao H.K.; Chen J. (My University, 2004)
In situ high-pressure synchrotron X-ray diffraction and infrared absorption experiments for gibbsite were performed at room temperature up to 53 and 25 GPa, respectively. A phase transition was confirmed at about 2.5 GPa. The high-pressure phase is indexed as an orthorhombic structure, rather than a triclinic structure as reported in previous studies. The compressibility of gibbsite and its high-pressure polymorph were studied, and their bulk moduli K0 were determined to be 49 and 75 GPa, respectively with K0' as 4. The in situ high-pressure infrared absorption spectra revealed the gradual disordering of hydrogen substructure above 15 GPa in quasihydrostatic compression.
Keywords: AL(OH)3; HIGH-PRESSURE; PHASE TRANSITION; X-RAY DIFFRACTION; INFRARED ABSORPTION